Pendampingan Remaja Dalam Pencegahan Dismenorea Melalui Senam Dismenorea Di Kabupaten Bulukumba: Pendampingan Remaja Dalam Pencegahan Dismenorea Melalui Senam Dismenorea Di Kabupaten Bulukumba - Jusni; Arfiani arfi; Kurniati Akhfar kurni; Haerani rani (JCS, 2023)
Adolescence is a dynamic phase of development in a person's life. This period is a transition period from childhood to adulthood which is marked by accelerated physical, mental, emotional, and social development. One of the changes that occur when they reach adulthood in young women is the occurrence of menstruation, although menstruation is a natural process experienced by women, this becomes a major problem in society if menstrual disorders occur. The activity of assisting adolescents in controlling dysmenorrhoea pain through dysmenorrhoea exercise in Bulukumba Regency aims to increase the knowledge of young women about dysmenorrhea and how to control it. This community service is carried out by providing information about dysmenorrhea and mentoring on how to do dysmenorrhea exercises with a total of 20 participants. This community service uses communicative technique methods with three approaches, namely lectures, demonstrations, questions and answers and discussions. The results of adolescent mentoring activities in controlling dysmenorrhea through dysmenorrhoea exercise are very influential in improving midwifery care services for adolescents to increase adolescent knowledge and skills in controlling dysmenorrhea independently. With this assistance, it is expected to be able to increase the knowledge and skills of adolescents about dysmenorrhoea exercise as an effort to control dysmenorrhea so that productive youth programs can be realized.